2014
DOI: 10.4161/auto.36182
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in osteoblasts is involved in mineralization and bone homeostasis

Abstract: Bone remodeling is a tightly controlled mechanism in which osteoblasts (OB), the cells responsible for bone formation, osteoclasts (OC), the cells specialized for bone resorption, and osteocytes, the multifunctional mechanosensing cells embedded in the bone matrix, are the main actors. Increased oxidative stress in OB, the cells producing and mineralizing bone matrix, has been associated with osteoporosis development but the role of autophagy in OB has not yet been addressed. This is the goal of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
308
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(336 citation statements)
references
References 80 publications
13
308
0
3
Order By: Relevance
“…Recently, the role of autophagy in bone physiology and pathophysiology has gradually been unmasked. The effects of autophagy modulators in bone health and osteoblastic differentiation have been widely studied [32], and recent studies have demonstrated that autophagy deficiency compromises osteoblast mineralization in vitro and in vivo [33, 34]. Because bone and dentin share similar components, it is necessary to investigate the role of autophagy in dentin regeneration and odontoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of autophagy in bone physiology and pathophysiology has gradually been unmasked. The effects of autophagy modulators in bone health and osteoblastic differentiation have been widely studied [32], and recent studies have demonstrated that autophagy deficiency compromises osteoblast mineralization in vitro and in vivo [33, 34]. Because bone and dentin share similar components, it is necessary to investigate the role of autophagy in dentin regeneration and odontoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,55 For example, cultures of autophagy gene-knockout osteoblasts (BECN-1, ATG7 e LC3) result in deficiency in the process of mineralization. 56 In vitro studies show that pharmacological inhibition of autophagy in osteoblast-like cells increases oxidative stress and stimulates apoptosis in these cells. In contrast, induction of autophagy in cultures of osteoblast-like cells reduces their oxidative stress and inhibits apoptosis.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…Studies have reported that autophagy can be induced by various nanoparticles in osteoblasts, can promote the differentiation and mineralization of osteoblasts, 36,42 can protect osteoblasts from oxidative damage and apoptosis, 43 and can play essential roles in bone homeostasis. 44 Our present results indicate that Ta-NPs should be added to this nanoparticle list.…”
mentioning
confidence: 99%